Adult onset supranuclear ophthalmoplegia, cerebellar ataxia, and neurogenic proximal muscle weakness in a brother and sister: another hexosaminidase A deficiency syndrome. Issue 6 (June 1987) - Harding, A E; Young, E P; Schon, F
Abstract : An Ashkenazi Jewish brother and sister developed progressive ataxia and proximal neurogenic muscle weakness, associated with supranuclear ophthalmoplegia, in the fourth decade of life. Hexosaminidase A activity, assayed using both synthetic and natural substrates, was severely reduced in the patients' plasma, leukocytes, and skin fibroblasts. Enzyme activity in their parents was in a similar range to that seen in heterozygotes for Tay-Sachs disease. The increasing evidence for marked clinical and molecular heterogeneity in the GM2 gangliosidoses warrants their consideration in the diagnosis of multisystem degenerative neurological disorders, even if onset of symptoms is in adult life.